Pelatihan Public Speaking untuk Meningkatkan Komunikasi dan Kepercayaan Diri Siswa Sekolah Menengah Kejuruan dalam Dunia Kerja - Budiati; Fisthyta Hilda Irawan; Indah Sukma Wahyuni; Thabita Juliani Vierdasari; Christian Dede Navy Saputra (Insan Kreasi Media, 2025)
Public speaking is essential for vocational high school (SMK) students as it enhances soft skills, thereby enabling effective communication in a competitive labor market and in social interactions. Mastery of public speaking fosters self-confidence, leadership, and the ability to convey ideas clearly to diverse audiences. This community service program aimed to provide practical public speaking training while also enhancing students’ self-confidence and communication skills. This community service was service-learning method with training and assistance approach that involving the lecturer and students to take a part actively in the activity. The training was designed to include the delivery of basic knowledge and techniques of public speaking (speech), as well as hands-on practice sessions. At the conclusion of the program, students demonstrated noticeable improvements in confidence, clarity of expression, and overall public speaking performance. Practical training in public speaking effectively contributes to the development of vocational high school students’ soft skills, preparing them to communicate more effectively in academic, professional, and social contexts.